2019
DOI: 10.3114/fuse.2019.03.04
|View full text |Cite
|
Sign up to set email alerts
|

Miracula Moenusica , a New Member of the Holocarpic Parasitoid Genus from the Invasive Freshwater Diatom Pleurosira Laevis

Abstract: Holocarpic oomycetes are poorly known but widespread parasites in freshwater and marine ecosystems. Most of the holocarpic species seem to belong to clades that diverge before the two crown lineages of the oomycetes, the Saprolegniomycetes and the Peronosporomycetes. Recently, the genus Miracula was described to accommodate Miracula helgolandica, a holocarpic parasitoid of Pseudo-nitzschia diatoms, which received varying support for its placement as the earliest-diverging oomycete lineage. In the same phylogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…Diatom samples were collected from the River Main, Frankfurt am Main, Germany (N50°06.195', E008°40.323') as described previously (Buaya & Thines 2019). Approximately 10 mL of biofilm suspension was poured into each of several 15 mL Petridishes, and screened for infected diatoms using a compound inverted light microscope (AE31, Motic, USA).…”
Section: Sampling Isolation and Microscopymentioning
confidence: 99%
See 1 more Smart Citation
“…Diatom samples were collected from the River Main, Frankfurt am Main, Germany (N50°06.195', E008°40.323') as described previously (Buaya & Thines 2019). Approximately 10 mL of biofilm suspension was poured into each of several 15 mL Petridishes, and screened for infected diatoms using a compound inverted light microscope (AE31, Motic, USA).…”
Section: Sampling Isolation and Microscopymentioning
confidence: 99%
“…In contrast, the olpidiopsidoid parasitoid of Pseudo-nitzschia spp. was initially suspected to be a member of either Ectrogella or Olpidiopsis (Hanic et al 2009), but was found to be the earliest diverging oomycete lineage in Buaya et al (2017) and consequently assigned to the new genus Miracula as Miracula helgolandica, to which a second, limnic species was recently added (Buaya & Thines 2019). A recent study (Buaya et al 2019b) has shown that the genus Olpidiopsis, with its type species, O. saprolegniae, is largely unrelated to the diatom parasites currently placed in the genus, necessitating a taxonomic revision.…”
Section: Introductionmentioning
confidence: 99%
“…After repeated cycles of infection for about 3 months the diatom/pathogen combination with the most steady infection rate was chosen for longterm cultivation as described above. Microscopy was performed as described previously [22] using an inverted microscope (AE30, Motic, Hong-Kong, China) for regular checks and subcultivation and a Zeiss Imager2 (Carl Zeiss, Jena, Germany) for microscopic images. For continuous supply of the host, CGS1 and CG36 were grown in 6 cm Petri dishes, and about 10 cells were transferred to new Petri dishes with marine f/2 medium every 2 weeks to maintain the diatom cultures.…”
Section: Methodsmentioning
confidence: 99%
“…This means that the entire thallus is converted into a sporangium upon maturity [12][13][14][15][16][17][18]. Many of these species are parasitoids, and kill their hosts during colonisation [19][20][21][22][23]. Lagenisma coscinodisci is one of these parasitoids [15,20,24] and is characterised by forming a branched thallus with stout hyphae in hosts of the large centric diatom genus Coscinodiscus.…”
Section: Introductionmentioning
confidence: 99%
“…The Coscinodiscophyceae parasitoid L. coscinodisci was found to belong to the basal Saprolegniomycetes (Thines et al 2015). Miracula helgolandica was inferred to Section Editor: Marc Stadler be the earliest-diverging oomycete lineage together with the recently described freshwater parasitoid M. moenusica, while D. drebesii formed a monophyletic group together with D. gillii and uncultured environmental sequences (Buaya and Thines 2019;Buaya et al 2017;2019a). Only recently, phylogenetic affinities of the genus Olpidiopsis and Ectrogella were resolved and their type species epitypified, leading to the taxonomic revisions of these two important taxa of early-diverging oomycetes (Buaya et al 2019c; Buaya and Thines 2020).…”
Section: Introductionmentioning
confidence: 99%